DiGi Corporate Social Responsibility: A Case Study - Abdo, Lina Abdulmalek Saeed (2010)
Corporate social responsibility strategy and competitive advantage are important issues for the contemporary discussion on corporations in society. This study addresses CSR implementation in practice by first understanding a firm’s corporate social responsibility motives, then exploring how these motives translate to CSR programmes and their alignment to core business and strategy. The objective of the study is met through studying relevant literature and the implementation of practical research. The latter was carried out through a case study of DiGi Telecom; the company brands itself as sustainable company and was the only telecom company in Malaysia to publish a sustainability report in 2009. The research used informal interviews with Vimal L Kumar (Head of Corporate Responsibility) and Susan Tam (Corporate Responsibility staff member) as well as content analysis of DiGi’s sustainability report, website material and other documents. This research concludes that the main motive for DiGi to engage in CSR is strategic, due to recent market and non-market changes. The company’s main focus is environment and climate change, which is in line with the mother company’s (Telenor ASA) CSR focus. The research also concludes that, while there is evidence of “somewhat” strategic CSR in the company, it is still lacking a materiality assessment and measurement of the positive and negative impacts on communities. This has yielded an ad hoc approach to chosen CSR initiatives. The study is expected to contribute to literature by providing implications for business in using a more strategic approach towards CSR and management as well as presenting feedback to DiGi on its first published sustainability report for further improvement.